The Preimplantation Psychosocial Evaluation and Prediction of Clinical Outcomes During Mechanical Circulatory Support: What Information Is Most Prognostic?. Issue 3 (27th April 2020) - Dew, Mary Amanda; Hollenberger, Jennifer C.; Obregon, Laura L.; Hickey, Gavin W.; Sciortino, Christopher M.; Lockard, Kathleen L.; Kunz, Nicole M.; Mathier, Michael A.; Ramani, Ravi N.; Kilic, Arman; McNamara, Dennis M.; Simon, Marc A.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Psychosocial evaluations are required for long-term mechanical circulatory support (MCS) candidates, no matter whether MCS will be destination therapy (DT) or a bridge to heart transplantation. Although guidelines specify psychosocial contraindications to MCS, there is no comprehensive examination of which psychosocial evaluation domains are most prognostic for clinical outcomes. We evaluated whether overall psychosocial risk, determined across all psychosocial domains, predicted outcomes, and which specific domains appeared responsible for any effects. Methods: A single-site retrospective analysis was performed for adults receiving MCS between April 2004 and December 2017. Using an established rating system, we coded psychosocial evaluations to identify patients at low, moderate, or high overall risk. We similarly determined risk within each of 10 individual psychosocial domains. Multivariable analyses evaluated whether psychosocial risk predicted clinical decisions about MCS use (DT versus bridge), and postimplantation mortality, transplantation, rehospitalization, MCS pump exchange, and standardly defined adverse medical events (AEs). Results: In 241 MCS recipients, greater overall psychosocial risk increased the likelihood of a DT decision (odds ratio, 1.76; P = 0.017); and postimplantation pump exchange and occurrence of AEs (hazard ratios [HRs] ≥ 1.25; P ≤ 0.042). The individual AEs most strongly predicted were cardiac arrhythmias and device malfunctions (HRs ≥ 1.39; P ≤ 0.032). The specific psychosocial domains predicting at least 1 study outcome were mental health problem severity, poorer medical adherence, and substance use (odds ratios and HRs ≥ 1.32; P ≤ 0.010). Conclusions: The psychosocial evaluation predicts not only clinical decisions about MCS use (DT versus bridge) but important postimplantation outcomes. Strategies to address psychosocial risk factors before or soon after implantation may help to reduce postimplantation clinical risks.